Performance of coconut (Cocos nucifera L.) hybrids for yield and quality in the Utkal plain region of Odisha state, India - Sahoo, S. C.; Sumitha, S.; Karna, A. K.; Mishra, G.; Maheswarappa, H. P. (Journal of Plantation Crops, 2021)
Cocos nucifera L. is a perennial oil yielding crop with a long productive life span (>60 years); thus, identifying a suitable high yielding hybrid to a particular agro-climatic region plays a prime role in achieving sustainable coconut yield. In this context, an evaluation trial with varietal cross combinations involving Tall × Dwarf (six crosses) and Dwarf × Tall (two crosses) was conducted at All India Coordinated Research Project (AICRP) on Palms, Bhubaneshwar Centre, Odisha, for 15 years. The experiment was laid out in randomized block design with four replications maintaining six palms per replication. Observations on yield and yield attributing characters during 2018 to 2020 revealed the superior performance of ECT × GBGD (99.1 nuts), which was followed by ECT × MYD (86.9 nuts) over the local check (ECT) by recording higher nut yield. Copra output per palm was significantly the highest under ECT × GBGD (20.6 kg palm-1), followed by LCT × COD (18.6 kg palm-1). Hybrids possessed a higher quantity of organoleptically ‘good’ tender nut water (270.3 to 354.1 mL) with TSS of 5.8 to 6.9 °Brix, 25.4 to 34.0 ppm of sodium and 2065.9 to 2885.0 ppm of potassium.